Analisis Perkembangan Identitas Sosial Anak dalam Lingkungan Multikultural: Penelitian - Nenesia Okvaiv Adesta; Juliana Batubara; Nurfarida Deliani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
An environment rich in cultural diversity plays an important role in shaping children's social identities from an early age. The diversity of cultures, ethnicities, languages, and values present in daily interactions has a significant impact on how children see themselves and others. This study aims to explore the impact of a multicultural environment on children's social identity development and to identify supporting and hindering factors for students at IT Sabbihisma High School. For this research, the method applied is descriptive qualitative, with data collected thru observation, in-depth interviews, and documentation related to children's social development and multicultural education. Analysis findings indicate that direct interaction with diversity can strengthen empathy, tolerance, inclusive attitudes, and children's ability to build a positive social self-concept. The family, school, and peer environment serve as key elements that strengthen the development of social identity in a multicultural context. However, the presence of stereotypes, social prejudice, and a lack of understanding of culture can be obstacles in this process. This research emphasizes the importance of planned multicultural encouragement thru inclusive educational and parenting approaches to maximize children's social identity development.